A randomized controlled trial to explore the efficacy and safety of transcranial direct current stimulation on patients with post-stroke fatigue. Issue 41 (15th October 2021) - Dong, Xiang-Li; Sun, Xing; Sun, Wei-Ming; Yuan, Qin; Yu, Guo-Hua; Shuai, Lang; Yuan, Ye-Feng
Abstract: Background: Post-stroke fatigue seriously affects the quality of life for stroke patients. There is no effective treatment at present. transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation which may have therapeutic effect on post-stroke fatigue. This study will explore about this. Method: A total of 60 patients with post-stroke fatigue were randomly divided into the control group and the treatment group with 30 patients each by minimization randomization. Both groups received basic treatment and conventional rehabilitation. In the treatment group, patients were treated with active tDCS, while in the control group, sham tDCS. Both active and sham tDCS were administered 6 times a week for 4 weeks. Before and after the trial, the Fatigue Severity Scale (FSS), Fugl-Meyer Assessment (FMA) and Modified Barthel Index (MBI) were evaluated and analyzed. And comparisons were made among groups. And there were an 8-week follow-up after the intervention. Result: Before the intervention, there were no significant differences in baseline data and assessment scores between the groups (P > 0.05). After 4 weeks of intervention, FSS scores in the treatment group were significantly lower than those in the control group (P = 0.012), and FMA and BMI scores were significantly higher than those in the control group (P < 0.05). There was no significant change in FSS scores after 8 months of follow-up (P > 0.05). Discussion: TDCS is a safe treatment that can effectively reduce the degree of fatigue after stroke, improve the motor function and daily activity ability of patients after stroke, and the efficacy is better than only routine rehabilitation training. Trial registration number: Chinese Clinical Trial Registry, ChiCTR2000031120. Registered on March 22, 2020.